2012
DOI: 10.1371/journal.pone.0033975
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cholinesterases in Plasma of Three Portuguese Native Bird Species: Application to Biomonitoring

Abstract: Over the last decades the inhibition of plasma cholinesterase (ChE) activity has been widely used as a biomarker to diagnose organophosphate and carbamate exposure. Plasma ChE activity is a useful and non-invasive method to monitor bird exposure to anticholinesterase compounds; nonetheless several studies had shown that the ChE form(s) present in avian plasma may vary greatly among species. In order to support further biomonitoring studies and provide reference data for wildlife risk-assessment, plasma choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…However, blood AChE histochemistry was assessed [ 56 ], and AChE activity was analysed for the purpose of determining the effects of daily photoperiods, a behaviour biomarker of organophosphate (OP) exposure, to establish the basal levels, compare the response to organophosphate and carbamate exposure, and compare the age-dependent changes in plasma [ 19 , 20 , 21 , 57 , 58 , 59 , 60 ]. Furthermore, plasma cholinesterases were characterised to establish the basal activities [ 34 , 61 ]. There is wide variation in AChE activity interspecies [ 57 ] and between matrices, pointing out the need to determine the basal AChE activity in plasma and S9 in white stork nestlings.…”
Section: Resultsmentioning
confidence: 99%
“…However, blood AChE histochemistry was assessed [ 56 ], and AChE activity was analysed for the purpose of determining the effects of daily photoperiods, a behaviour biomarker of organophosphate (OP) exposure, to establish the basal levels, compare the response to organophosphate and carbamate exposure, and compare the age-dependent changes in plasma [ 19 , 20 , 21 , 57 , 58 , 59 , 60 ]. Furthermore, plasma cholinesterases were characterised to establish the basal activities [ 34 , 61 ]. There is wide variation in AChE activity interspecies [ 57 ] and between matrices, pointing out the need to determine the basal AChE activity in plasma and S9 in white stork nestlings.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the importance of the current study in establishing the range of plasma ChE activity in non-exposed vultures is crucial, particularly when endangered or protected species are involved. Several studies underscore the need to establish reference values of ChE activity in the brain and plasma of birds against which the effects of anti-ChE pesticides may be compared (Gee et al 1981, Gard & Hooper 1993, Montesinos et al 1997, Mayack & Martin 2003, Rend on-von Osten et al 2005, Roy et al 2005, Fildes et al 2009, Santos et al 2012, Oropesa et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that different forms of ChEs show different sensitivity to anti-ChE agents. ChE characterization in animals is usually performed using different substrates (acetylthiocholine iodide, propionylthiocholine iodide and S-butyrylthiocholine iodide) and selective inhibitors (eserine sulphate, iso-OMPA and BW284C51) (Rend on-von Osten et al 2005, Santos et al 2012, Oropesa et al 2013. Results of this characterization have shown that there are two types of ChEs: acetylcholinesterase (AChE; EC 3.1.1.7), which has high specificity for acetylcholine and is present in nervous tissue and blood of vertebrates, and butyrylcholinesterase (BChE; EC 3.1.1.8), which is a non-specific B esterase found essentially in the plasma of many vertebrates.…”
mentioning
confidence: 99%
“…Published avian reference ranges for plasma ChE and brain AChE are numerous (Westlake et al 1981;Hill 1988;Gard and Hooper 1993;Tully et al 2003;Fildes et al 2009;Santos et al 2012;Shimsoni et al 2012;Grossett et al 2014). However, a consistently reported recommendation is the need for species-specific and laboratory-specific reference ranges (Hill 1988;Shimsoni et al 2012).…”
Section: Discussionmentioning
confidence: 99%